Fabrication of highly effective hybrid biofuel cell based on integral colloidal platinum and bilirubin oxidase on gold support. Issue 1 (December 2018) - Hasan, Md; Kuis, Robinson; Narayanan, J.; Slaughter, Gymama
Abstract A hybrid biofuel cell (HBFC) is explored as a low-cost alternative to abiotic and enzymatic biofuel cells. Here the HBFC provides an enzymeless approach for the fabrication of the anodic electrode while employing an enzymatic approach for the fabrication of the cathodic electrode to develop energy harvesting platform to power bioelectronic devices. The anode employed 250 μm braided gold wire modified with colloidal platinum (Au-co-Pt) and bilirubin oxidase (BODx) modified gold coated Buckypaper (BP-Au-BODx) cathode. The functionalization of the gold coated multi-walled carbon nanotube (MWCNT) structures of the BP electrodes is achieved by 3-mercaptopropionic acid surface modification to possess negatively charged carboxylic groups and subsequently followed by EDC/Sulfo-NHS (1-Ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-Hydroxysulfosuccinimide) crosslinking with BODx. The integration of the BODx and gold coated MWCNTs is evaluated for bioelectrocatalytic activity. The Au-co-Pt and BP-Au-BODx exhibited excellent electrocatalytic activity towards glucose oxidation with a linear dynamic range up to 20 mM glucose and molecular oxygen reduction, respectively. The HBFC demonstrated excellent performance with the largest open circuit voltages of 0.735 V and power density of 46.31 μW/cm2 in 3 mM glucose. In addition, the HBFC operating on 3 mM glucose exhibited excellent uninterrupted operational stability while continuously powering a small electronic device. These results provide great opportunities for implementing this simple but efficient HBFC to harvest the biochemical energy of target fuel(s) in diverse medical and environmental applications.